MENAKAR PEMIKIRAN FIQIH SOSIAL M.A. SAHAL MAHFUDH UNTUK KEMASLAHATAN UMAT - Muh - Rusli (LPPM IAIN Sultan Amai Gorontalo, 2021)
This article discusses M.A. Sahal Mahfudh’s thought on jurisprudence. It is by focusing on the importance of the dynamic on the fiqh-legal products. Fiqh is capable of dialoguing with the plurality of reality with no override authority of the text. Nuance social jurisprudence is a thought that maintains existing legal method but adopted patterns of thinking and new methods in the process of developing jurisprudence. Fiqh is not just a social tool to see each issue of white sunglasses, but rather as a paradigm established juristic meaning socially. It should lead the ummah to understand its contexts. We supposed not get stuck on the formalistic assumption to the jurisprudence. Therefore, the jurists should have a high social sensitivity as a basis for determining a product of jurisprudence. The most important thing in the development of fiqh is the achievement of the five goals in the principles of Islamic law (maqasid al-Shari'ah) which maintains religion, mind, soul, lineage (descent) and property. Eventually, jurisprudence will lead men to happiness in this world and in the hereafter.